Correlation of peripapillary retinal nerve fibre layer thickness with visual acuity in paediatric patients affected by optic pathway glioma. Issue 8 (3rd October 2018) - Parrozzani, Raffaele; Miglionico, Giacomo; Leonardi, Francesca; Pulze, Serena; Trevisson, Eva; Clementi, Maurizio; Opocher, Enrico; Licata, Viviana; Viscardi, Elisabetta; Pilotto, Elisabetta; Frizziero, Luisa; Midena, Edoardo
Abstract: Purpose: To evaluate peripapillary retinal nerve fibre layer (RNFL) thickness, measured by spectral‐domain optical coherence tomography (SD‐OCT), as a surrogate of visual function in a population of paediatric patients affected by optic pathway glioma (OPG) associated with neurofibromatosis type 1 (NF1). Methods: A total of 38 paediatric patients (66 eyes) affected by MRI‐proven OPG were included. Each patient underwent complete ophthalmological examination, including age‐appropriate visual acuity (VA) assessment and RNFL analysis by SD‐OCT. Visual acuity was classified as normal or pathologic using age‐based normative data. Visual acuity was correlated to mean RNFL thickness of the whole peripapillary area and of each single analyzed sector (nasal, superior, temporal, inferior). Results: Visual acuity was normal in 43 (65%) and pathologic in 23 (35%) eyes. Mean parapapillary RNFL thickness of each analyzed sector was significantly lower in eyes with abnormal VA (p < 0.05). The best balanced cut‐off value of global RNFL thickness allowing to discriminate between eyes with normal and pathologic VA was 76.25  μ m (91%, 76%, 67% and 94% of sensitivity, specificity, positive and negative predicting value, respectively). Considering best balanced cut‐off values of other analyzed RNFL sectors, the superior (p = 0.0029) and the inferior (p = 0.0024) sectors reached the higher sensitivity (87% and 87%, respectively) and specificity (81% and 79%, respectively). Conclusion: Retinal nerve fibre layer thickness is directly related to VA in children affected by NF1‐related OPG, and should be considered as a potential surrogate marker of VA. Retinal nerve fibre layer thickness cut‐off values can be used in paediatric patients to discriminate false‐positive results obtained by VA measurement.